Anxiety and depression as potential risk factors for limited pain management in patients with elderly knee osteoarthritis: a cross-lagged study - Wenhao Yang; Guangyuan Ma; Jingchi Li; Taiyuan Guan; Dingchang He; Dujiang Yang; Guoyou Wang; Hui Shi (BMC Musculoskeletal Disorders)
Abstract Background Pain management for knee osteoarthritis (KOA) patients is challenging. Pain arises from both physiological and psychological interactions, with anxiety and depression potentially contributing as risk factors that hinder effective pain management in KOA patients. Methods Before treatment(T1), A total of 206 elderly inpatients with KOA were enrolled based on initial screening criteria. After treatment (T2), patients were selected based on inclusion and exclusion criteria, and completed follow-up through phone or online questionnaires. The interval between T1 and T2 was three months. Outcome measures included the Visual Analogue Scale (VAS) for pain intensity, Beck Anxiety Inventory (BAI) for anxiety, and Geriatric Depression Scale (GDS) for depression. Descriptive and bivariate analyses were used to evaluate the pain, anxiety and depression of the participants. A cross-lagged model was used to examine the temporal and causal associations among pain, anxiety, and depression. Results 91% of elderly patients with KOA experienced at least mild depression. Furthermore, 31% of patients reported mild or higher levels of anxiety. At the same time, pain, depression, and anxiety were significantly correlated and mutually predictive(all p < 0.01). Across the different time points, Depression and anxiety at T1 positively predicted pain at T2,with correlation coefficients of 0.19 (p < 0.05) and 0.07 (p < 0.05), respectively. Conclusions Anxiety and depression may be potential risk factors limiting the effectiveness of pain management in KOA patients. Clinical treatment should regularly evaluate anxiety and depression levels and integration of psychological interventions or appropriate antianxiety and antidepressant medications. Clinical trial number Not applicable, for the investigative research nature of the study.